Nanozymes as efficient tools for catalytic therapeutics. Issue 2 (13th July 2021) - Liu, Shengda; Xu, Jiayun; Xing, Yunpeng; Yan, Tengfei; Yu, Shuangjiang; Sun, Hongcheng; Liu, Junqiu
Abstract: Nanozymes are emerging nanomaterials with ideal enzymatic catalytic performance. The development of nanozymes has been shown clear potential to overcome the limitations of natural enzymes such as troublesome preparation, ease of denaturation, high price, and difficulty of recycling. Since the discovery of magnetic Fe3 O4 nanoparticles with intrinsic peroxidase‐like activity in 2007, the researches on nanozymes have been booming in the next decade. According to the unique nanoscale effect, nanozymes show prominent catalytic performance, which enables them to be applied in various fields of biomedical engineering. In this review, we mainly focus on the catalytic therapeutics of nanozymes in combating bacteria, cancer therapy, alleviating inflammation and neuroprotection. Abstract : The applications of nanozymes in biomedical fields have attracted extensive attention. In this mini‐review, Junqiu Liu and coworkers focus on the catalytic therapeutics of nanozymes in combating bacteria, cancer therapy, alleviating inflammation, and neuroprotection.